2007
DOI: 10.1016/j.colsurfa.2006.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phosphate at the aluminum (hydr)oxides–water interface: Role of the surface acid–base properties

Abstract: In this paper, the adsorption of phosphate on two crystallized aluminum oxides, pseudo-boehmite (pseudo-␥-AlOOH) and ␣-Al 2 O 3 , was studied. The adsorption experiments were carried out in 0.01 M KNO 3 solutions at pH 4 and 6, respectively. Adsorption densities were calculated to evaluate the phosphate adsorption affinity for the two aluminum oxides. To better understand the effect of surface properties on the adsorption behavior of phosphate, the surface structure and properties were investigated with X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…Figure 1 shows the XRD results of the sample. The main diffraction peaks can be indexed as boehmite AlOOH 22, 23. The very sharp peaks indicate high crystallinity of the synthesized product.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the XRD results of the sample. The main diffraction peaks can be indexed as boehmite AlOOH 22, 23. The very sharp peaks indicate high crystallinity of the synthesized product.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that, for three different Mg/Al-LDHs biochar composites, the equilibrium pH of each composite-related filtrate was higher than the initial pH from 3 to 9, and lower than the pH from 9 to 11. This can be attributed to the acid-base properties of hydroxyl groups on adsorbent surface, which resulted in the protonation or deprotonation of its structure (Lǚ et al, 2013;Yang et al, 2007). The positively protonated Mg/Al-LDHs surface was favored for phosphate adsorption.…”
Section: Effect Of Ph On the Phosphate Adsorptionmentioning
confidence: 99%
“…making them harder to react with phosphate. 14,35 Hence, the phosphate adsorption on T600 was better under neutral and acidic conditions.…”
Section: Effect Of Phmentioning
confidence: 99%